2013
DOI: 10.1177/1534508413511848
|View full text |Cite
|
Sign up to set email alerts
|

Examining Teachers’ Use of Evidence-Based Practices During Core Mathematics Instruction

Abstract: The extent to which teachers implement evidence-based practices, such as explicit instruction, is critical for improving students' mathematics achievement. The purpose of this study was to examine the effect of the kindergarten Early Learning in Mathematics (ELM) curriculum on teachers' use of explicit mathematics instruction in core educational settings. Observation data for the study were collected during a randomized controlled trial designed to investigate the efficacy of the ELM curriculum. A multifaceted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…These findings suggest that ELM significantly increased the use of evidence-based teaching practices for teachers who served as control teachers in the year prior. These results are noteworthy because they lend support not only to the robustness of the reported effects in Doabler et al (2014) Note. ELM = Early Learning in Mathematics; CON-ELM = control-ELM group; CE = CON-ELM group; EE = ELM-ELM group.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…These findings suggest that ELM significantly increased the use of evidence-based teaching practices for teachers who served as control teachers in the year prior. These results are noteworthy because they lend support not only to the robustness of the reported effects in Doabler et al (2014) Note. ELM = Early Learning in Mathematics; CON-ELM = control-ELM group; CE = CON-ELM group; EE = ELM-ELM group.…”
Section: Discussionsupporting
confidence: 59%
“…While preliminary, the findings of Doabler et al (2014) demonstrated initial promise of the ELM program to increase teachers' use of evidence-based teaching practices during core mathematics instruction. Yet, it is unclear from this earlier work whether the statistically significant differences found between the treatment (i.e., ELM) and control (i.e., standard district mathematics instruction) classrooms were based on ELM teachers implementing the program according to its design or whether ELM teachers simply utilized explicit teaching practices acquired in their prior teaching experience.…”
Section: Instructional Design and Its Role In Evidence-based Teachingmentioning
confidence: 90%
See 1 more Smart Citation
“…One promising study is by Doabler et al (2014) on the results of an evidence‐led curriculum, in which it is assumed that teachers can follow the curriculum without being aware of the audit trail leading back to the evidence for its use. The study involved around 2,700 students in 46 schools in Oregon and Texas.…”
Section: Enforced Use Of Evidencementioning
confidence: 99%
“…Bacher-hicks, Chin, & Hill, n.d.;Bill & Melinda Gates foundation, 2012;Blazar, 2015;Hill, 2014;Hill et al, 2008;Hill & Chin, n.d.;Hill, Kapitula, & Umland, 2011;Hill, Umland, Litke, & Kapitula, 2012;Kane et al, 2014;Kelcey, Mcginn, Hill, & Charalambous, n.d The QCI was developed in the same study as the RCMIS and was developed to examine the impact of the kindergarten Early Learning in Mathematics (ELM) curriculum on teaching behavior. The QCI measures eight aspects of explicit instructional interactions and was designed to complement a frequency-based instrument, the COSTI-M. Doabler et al, 2015;Doabler, Nelson, et al, 2014; Early Learning in Mathematics Implementation Fidelity Observation, n.d.…”
Section: Research Into the Cos (For Each Publication)mentioning
confidence: 99%